Soil fertility and pH measuring tool for paddy soil using internet of things technology - Sujono -; Umi Kulsum Nur Qomariah (Universitas Trunojoyo Madura, 2025)
Agriculture is a vital sector that is a food security sector. However, agricultural productivity is still often hampered by the lack of monitoring of soil conditions, which results in inaccurate fertilizer application. The development of an Internet of Things-based fertility measuring tool is an innovative solution to overcome this problem. With the ability to provide accurate data on N, P, K and pH nutrient levels quickly, this tool allows farmers to fertilize precisely. The research method used is Research and Development which has stages of literature study, system design, web application development, calibration and testing: data analysis and improvement. Sandy soil samples L1, L3, and L4 nitrogen error 6–7%, phosphorus error 8–10%, potassium error 6–10%, and neutral soil pH slightly acidic error 5%. Clay soil samples L2, L6, L7, and L9, nitrogen and potassium content error 5–6% and 6–7%. Phosphorus error around 7%. Soil pH ranges from 3–5%, indicating slightly acidic conditions. Clay samples L5, L8, and L10 contain 5–10% nitrogen, 6–9% phosphorus, 6–8% potassium, and 3–5%. Therefore, the results of N, P, and K measurements on sandy, loamy, and clay soils should be interpreted with caution and confirmed through laboratory tests.